Establishment of a cardiac telehealth program to support cardiovascular diagnosis and care in a remote, resource-poor setting in Uganda. - Alyssa DeWyer; Amy Scheel; Jenipher Kamarembo; Rose Akech; Allan Asiimwe; Andrea Beaton; Bua Bobson; Lesley Canales; Kristen DeStigter; Dhruv S Kazi; Gene F Kwan; Chris T Longenecker; et al. (PLoS ONE, 2021)
Introduction To address workforce shortages and expand access to care, we developed a telemedicine program incorporating existing infrastructure for delivery of cardiovascular care in Gulu, Northern Uganda. Our study had three objectives: 1) assess feasibility and clinical impact 2) evaluate patient/parent satisfaction and 3) estimate costs. Methods All cardiology clinic visits during a two-year study period were included. All patients received an electrocardiogram and echocardiogram performed by a local nurse in Gulu which were stored and transmitted to the Uganda Heart Institute in the capital of Kampala for remote consultation by a cardiologist. Results were relayed to patients/families following cardiologist interpretation. The following telemedicine process was utilized: 1) clinical intake by nurse in Gulu; 2) ECG and echocardiography acquisition in Gulu; 3) echocardiography transmission to the Uganda Heart Institute in Kampala, Uganda; 4) remote telemedicine consultation by cardiologists in Kampala; and 5) communication of results to patients/families in Gulu. Clinical care and technical aspects were tracked. Diagnoses and recommendations were analyzed by age groups (0-5 years, 6-21 years, 22-50 years and > 50 years). A mixed methods approach involving interviews and surveys was used to assess patient satisfaction. Healthcare sector costs of telemedicine-based cardiovascular care were estimated using time-driven activity-based costing. Results Normal studies made up 47%, 55%, 76% and 45% of 1,324 patients in the four age groups from youngest to oldest. Valvular heart disease (predominantly rheumatic heart disease) was the most common diagnosis in the older three age groups. Medications were prescribed to 31%, 31%, 24%, and 48% of patients in the four age groups. The median time for consultation was 7 days. A thematic analysis of focus group transcripts displayed an overall acceptance and appreciation for telemedicine, citing cost- and time-saving benefits. The cost of telemedicine was $29.48/visit. Conclusions Our data show that transmission and interpretation of echocardiograms from a remote clinic in northern Uganda is feasible, serves a population with a high burden of heart disease, has a significant impact on patient care, is favorably received by patients, and can be delivered at low cost. Further study is needed to better assess the impact relative to existing standards of care and cost effectiveness.